2021
DOI: 10.1093/ajcn/nqab142
|View full text |Cite
|
Sign up to set email alerts
|

The association of maternal gestational hyperglycemia with breastfeeding duration and markers of milk production

Abstract: Background Previous studies focusing on the association between gestational diabetes and breastfeeding duration have been inconclusive. Objectives We aimed to determine whether maternal gestational hyperglycemia is associated with the duration of breastfeeding and the concentrations of markers linked to breastmilk production. Methods Data from the prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, the additional analyses found rather positive correlations between the body mass index at about 20 years of age and each measurement of breastfeeding history. Fifth, although evidence is insufficient [ 60 ], several observational studies showed that women with gestational diabetes are also less likely to initiate and maintain breastfeeding [ 60 , 61 ], which is another potential cause of reverse causality. Sixth, multiple comparisons of cardiovascular risk factors should have produced false-positive results, and thus, these analyses should be regarded as exploratory rather than confirmatory.…”
Section: Discussionmentioning
confidence: 99%
“…However, the additional analyses found rather positive correlations between the body mass index at about 20 years of age and each measurement of breastfeeding history. Fifth, although evidence is insufficient [ 60 ], several observational studies showed that women with gestational diabetes are also less likely to initiate and maintain breastfeeding [ 60 , 61 ], which is another potential cause of reverse causality. Sixth, multiple comparisons of cardiovascular risk factors should have produced false-positive results, and thus, these analyses should be regarded as exploratory rather than confirmatory.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures often sever milk ducts, thus disrupting milk removal and, over time, potentially isolating glandular tissue, causing milk stasis and ultimately apoptosis and regression of the tissue. Alternatively, in some instances breast implants may have been inserted into breasts that were already hypoplastic [73][74][75][76].…”
Section: Breast Anatomy and Milk Productionmentioning
confidence: 99%
“…The result of Herbert et al study (2021) showed that gestational diabetes was more common in American Indian, Alaska Natives, and Hispanic women than in black and non-Hispanic women (12% vs. 9%), and those with gestational diabetes had the lowest rates of exclusive breastfeeding (51% vs. 57–69%) compared to other women without gestational diabetes [ 4 ]. The results of many studies showed that stopping breastfeeding early was associated with many complications for the mother and the baby [ 6 18 ]. The results of Chertok et al study (2016) showed that there is a relationship between breastfeeding self-efficacy and the breastfeeding behavior of mothers.…”
Section: Introductionmentioning
confidence: 99%